The staff engineer's path : a guide for individual contributors navigating growth and change - Reilly, Tanya (O'Reilly Media, 2022)
For years, companies have rewarded their most effective engineers with management positions. But treating management as the default path for an engineer with leadership ability doesn't serve the industry well--or the engineer. The staff engineer's path allows engineers to contribute at a high level as role models, driving big projects, determining technical strategy, and raising everyone's skills. This in-depth book shows you how to understand your role, manage your time, master strategic thinking, and set the standard for technical work. You'll read about how to be a leader without direct authority, how to plan ahead to make the right technical decisions, and how to make everyone around you better, while still growing as an expert in your domain.